Правовые системы современных исламских государств в эпоху глобализации: особенности функционирования - Бехруз, Хашматулла Набієвич; Бехруз, Хашматулла Набієвич; Behruz, Hashmatulla (My University, 2011)
The globalisation is characterised as a determinating factor of social development, that stipulates increasing tendency of interaction between states, people and civilisations in this issue. Islam is considered as a fundamental component of social-political and legal-state development of modern Islamic states. The possibility of transformation of basic religious norms and principles on current stage is analysed.
Бехруз Хашматулла. Правовые системы современных исламских государств в эпоху глобализации: особенности функционирования / Хашматулла Бехруз // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C.296-304.
Keywords: правовые системы современных исламских государств; наднациональное право; национальная правовая система; исламская правовая доктрина; исламское право; правові системи сучасних ісламських держав; наднаціональне право; національна правова система; ісламська правова доктрина; ісламське право; legal systems of modern Islamic states; supranational law; national legal system; Islamic legal doctrine; Islamic law